dP/dtmax: An underestimated prognostic factor in large animal infarction model - Rita Garamvölgyi; Dénes Kőrösi; Ottó Tátrai; Emőke Bodor; Dániel Fajtai; Kornélia Farkas; András Vorobcsuk (Animal Models and Experimental Medicine)
Abstract The present study aims to establish a reproducible large animal experimental unit using a minipig model to monitor cardiac function changes. A 90‐min closed‐chest balloon occlusion of the left anterior descending branch of the coronary artery was used to induce myocardial infarction in Pannon minipigs. To monitor the cardiac function, measurements were made by cardiac magnetic resonance imaging (cMRI), invasive pressure monitoring, and a Pulse index Continuous Cardiac Output (PiCCO) hemodynamic system at 0, 72, and 720 h during the follow‐up period. End‐diastolic and end‐systolic volumes (EDV, ESV), left ventricular ejection fraction (LVEF) obtained by cMRI evaluation, global ejection fraction and aortic dP/dtmax obtained by the invasive method, were recorded and compared. The 72‐ and 720‐h EDV data showed a significant increase (p = 0.012, <0.001) compared to baseline, and the Day 30 data showed a significant increase compared to Day 3 (p = 0.022). The ESV 72 h after the infarction showed a significant increase (p = 0.001) compared to baseline, which did not change significantly by Day 30 (p = 0.781) compared to Day 3. EDV and ESV were significantly negatively correlated with aortic dpmax, and ESV was significantly correlated with LVEF. For LVEF and dPmax, a significant (p < 0.001 and p = 0.002) worsening was demonstrated at Day 3 compared to baseline, which was no longer statistically detectable for LVEF at Day 30 (p = 0.141), while the difference for dPmax was maintained (p = 0.002). The complementary use of PiCCO hemodynamic measurements in large animal models makes the previously used methodologies more robust and reliable.